The Evaluation of How Thematic Maps Created with Geographic Information Systems Effect the Success of Students - (:unkn) unknown (MARMARA UNIV, 2016)
This study was conducted in order to examine how thematic maps created with geographic information systems effect the success of 10th grade students. The study was implemented in 2015 together with 48 students in three high schools from Istanbul. An exercise was developed for the use of thematic maps by using 10.2 ArcGIS software. The quantitative data of the study were obtained from the pre-test and post-test. After implementing post-test, opinions of students about exercise were evaluated with the survey form. Paired sample t test was used to assess effect of thematic maps created with geographic information systems on the success of students. According to the pre and post-test results, using thematic maps created with geographic information systems differed. In accordance with the results obtained from the study, different thematic maps exercises should be developed and use of thematic maps should be increased in geography teaching.
Keywords: Thematic maps; GIS; secondary schools; geography teaching